The Use of Hounsfield Unit as a Quantitative Indicator for Detecting Stroke Phases on Non-Contrast Head CT-Scan - Achmad Bayhaqi Nasir Aslam; Dimas Noor Zulfikar Fauzi (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Ischemic stroke is a major cause of morbidity and mortality worldwide. Early determination of the stroke phase is essential for guiding appropriate management and predicting prognosis. Non-contrast head computed tomography (CT) remains the first-line imaging modality in acute stroke evaluation. Material and Methods: This analytic observational study with a cross-sectional approach was conducted at Dr. Saiful Anwar General Hospital, Malang, Indonesia. A total of 45 patients diagnosed with ischemic stroke were included and divided equally into three groups: acute, subacute, and chronic (15 patients each). HU values were measured using three regions of interest (ROIs) of 1 cm² placed within the infarcted area and averaged for analysis. Results: Mean HU values decreased progressively with stroke phase progression: acute 25.84 ± 1.07, subacute 18.11 ± 0.96, and chronic 9.24 ± 0.96. The Kruskal–Wallis test revealed a significant difference in HU values among the three groups (p < 0.001). Post hoc analysis using Dunn’s test confirmed significant differences between all phases (acute–subacute = 7.73 HU; subacute–chronic = 8.87 HU; acute–chronic = 16.60 HU; all p < 0.001). Clinically, decreased consciousness predominated in the acute phase (66.7%), while hemiparesis was more common in subacute (66.7%) and chronic (60%) phases, reflecting underlying tissue pathophysiology. Conclusion: Quantitative HU measurement on non-contrast CT provides a reliable and objective tool for differentiating ischemic stroke phases. The progressive decline in HU values corresponds with the temporal evolution of infarction, making HU analysis a useful adjunct to conventional qualitative CT interpretation.